Chemistry of dicationic diboranes - Widera, Anna; Filbeck, Erik; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2020)
Cationic monoboranes are commonly associated with elusive and highly electrophilic compounds used in modern organic synthesis. By contrast, only a few cationic diboranes are known and their chemistry comparatively underdeveloped. This review highlights some aspects of these species and their reactivity focusing primarily on especially stable guanidinate-bridged cations investigated by our group. Contrary to the intuitive presumption, sp2-hybridized cationic diboranes discussed herein serve not exclusively as Lewis acids, but also as two electron donors capable for reduction of organic π-acidic substrates. The latter proves them both as versatile synthetic reagents and valuable building blocks for the synthesis of remarkably stable macrocyclic structures with interesting electronic properties. The high tendency for formation of nonclassical multicenter bonding reflects in the dimerization behavior of cationic diborane species presented herein, leading to highly electron-deficient tetraboranes with unprecedented aromatic structures.